JURIDICAL REVIEW OF CONSUMER RIGHTS IN OBTAINING HALAL FOOD RIGHTS RELATED TO LAW NO. 8 YEAR 1999 - NURHADI, KHUSNUL MAULIDIYAH, MOH. KHOIRUL UMAM (Jurnal Independent, 2021)
ABSTRACT For consumers, information about goods and/or services has a very important meaning. The problems posed are how are the legal arrangements related to consumer rights in obtaining halal food products, how are the forms of supervision that can be carried out by the public on halal food products and how are the functions and duties of LP POM MUI in supervising the use of halal certificates. The results of the writing and discussion explain the legal arrangements related to consumer rights in obtaining halal food products according to national regulations is Law no. 8 of 1999 concerning Consumer Protection, Law no. 7 of 1996 concerning Food, PP No. 69/1999 concerning Food Labels and Advertisements and Kepmenkes No. 924/Menkes/SK/VIII/1996.